PENGARUH PENDIDIKAN KESEHATAN METODE DEMONSTRASI TERHADAP PELAKSANAAN CUCI TANGAN PADA PENUNGGU PASIEN - Triventiningtyas Triventiningtyas; Ana Farida Ulfa; Diah Ayu Fatmawati (Jurnal EDUNursing, 2021)
Abstract               Nosocomial infections can occur considering that hospitals as health care centers are warehouses of infectious pathogens "microbes". On the other hand, health workers can also be a source, in addition to the patient's family passing by, medical equipment and the hospital environment itself. Health education is a series of efforts aimed at influencing other people, ranging from individuals, groups, families and communities to carry out handwashing behavior. This study aims to determine the effect of health education demonstration method on the implementation of handwashing of patient caretakers at Asoka  of Jombang Hospital. The research design in this study is a quasi experiment. The population in this study were all the caretakers of High Care Unit patients at the Asoka, Jombang Hospital, an average of 70 people per month. The sampling technique used is purposive sampling. A sample of 40 people. The research variable consisted of the independent variable, namely health education, demonstration method using a questionnaire and the dependent variable, namely the implementation of handwashing for the patient waiting by using a questionnaire. Furthermore, the analysis was tested using the wilcoxon statistical test with = 0.05. The results of this study indicate that the implementation of handwashing of patient attendants in the treatment group was almost entirely good, 31 respondents (77.5%), the implementation of handwashing of patient attendants in the half control group was sufficient, as many as 20 respondents (50%). The results of the wilcoxon test obtained 0.000 < 0.005. The conclusion in this study is the effect of health education demonstration method on the implementation of handwashing of patient caregivers at the Asoka Pavilion, Jombang Hospital. Keyword : health education, demonstration method, hand washing